2016
DOI: 10.1093/hmg/ddw264
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association meta-analysis of diarrhoeal disease in young children identifiesFUT2locus and provides plausible biological pathways

Abstract: More than a million childhood diarrhoeal episodes occur worldwide each year, and in developed countries a considerable part of them are caused by viral infections. In this study, we aimed to search for genetic variants associated with diarrhoeal disease in young children by meta-analyzing genome-wide association studies, and to elucidate plausible biological mechanisms. The study was conducted in the context of the Early Genetics and Lifecourse Epidemiology (EAGLE) consortium. Data about diarrhoeal disease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 78 publications
1
21
0
Order By: Relevance
“…These HBGAs contain a carbohydrate structure, namely H type I antigen, whose synthesis is dependent on the FUT2 gene expression, which determines the secretor status. There is abundant evidence in the literature suggesting a strong association between the FUT2 gene and risk of infection with RV and other enteropathogens such as norovirus 5,49,50. Individuals with secretor phenotype have an increased susceptibility to RV, especially to P[8] genotype; conversely, severe RV gastroenteritis is virtually absent among children without FUT2 expression in the intestinal epithelium 51.…”
Section: The Role Of the Host In Rv Infectionmentioning
confidence: 99%
“…These HBGAs contain a carbohydrate structure, namely H type I antigen, whose synthesis is dependent on the FUT2 gene expression, which determines the secretor status. There is abundant evidence in the literature suggesting a strong association between the FUT2 gene and risk of infection with RV and other enteropathogens such as norovirus 5,49,50. Individuals with secretor phenotype have an increased susceptibility to RV, especially to P[8] genotype; conversely, severe RV gastroenteritis is virtually absent among children without FUT2 expression in the intestinal epithelium 51.…”
Section: The Role Of the Host In Rv Infectionmentioning
confidence: 99%
“…Non-secretors have a lower risk of diarrheal illness 2 and ear infections in childhood 3 . The non-secretor phenotype also confers resistance to specific pathogens that require FUT2 -dependent antigens to infect host cells, including Norovirus 4 7 , Rotavirus 8 11 and Helicobacter pylori 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Big data is a component in studies that have shown new precision characteristics of such public health concerns as cholera ( 141 ), chikungunya ( 142 ), diabetes ( 143 , 144 ), diarrhea ( 145 ), heatwave ( 146 ), influenza ( 147 ), opioid epidemic ( 148 , 149 ), preterm birth ( 150 ), stunting ( 151 ), and Zika ( 152 ).…”
Section: Understanding Diseasementioning
confidence: 99%